Tracking Changes in SARS-CoV-2 Transmission with a Novel Outpatient Sentinel Surveillance System in Chicago, Illinois, USA. (March 2022) - Richardson, R.; Arevalo, P.; Jorgensen, E.; Pacilli, M.; Lightner, S.; Cobey, S.; Gerardin, J.
Abstract : Purpose: Public health indicators typically used for monitoring the COVID-19 epidemic can be biased or lag behind changing community transmission patterns. Hospital admissions lag infection by 10 – 17 days, and test positivity rate is sensitive to changing availability of, access to, and demand for diagnostic testing. The U.S. city of Chicago investigated whether sentinel surveillance of recently symptomatic individuals receiving an outpatient diagnostic test for SARS-CoV-2 could provide early warning of increasing transmission. Methods & Materials: From May 2020 to June 2021, the Chicago Department of Public Health (CDPH) and Illinois Department of Public Health (IDPH) established community-based SARS-CoV-2 diagnostic testing sites throughout Chicago. From November 2020, these sites collected and reported patient data on symptom status and symptom onset date to CDPH and IDPH. Symptomatic individuals residing in Chicago who reported symptom onset within four days of diagnostic test were included in the sentinel population. COVID-19 case counts among the sentinel population were used to calculate the instantaneous reproductive number R(t) over time, which was compared to R(t) curves calculated from COVID-like illness (CLI) hospital admissions, CLI emergency department visits, and COVID-19-diagnosed emergency department visits. Pearson correlation between time-shifted sentinel case counts and each of these indicators was used to estimate the potential lead time provided by outpatient sentinel surveillance. Results: From November 1, 2020, to June 13, 2021, IDPH and CDPH collected a total of 15, 023 sentinel samples at community-based testing sites, an average of ∼470 samples per week. Trends in sentinel COVID-19 cases preceded CLI hospital admissions by 10 to 14 days. R(t) calculated from sentinel cases tracked well with R(t) calculated from CLI hospital admissions, CLI emergency department visits, and COVID-19-diagnosed emergency department visits. Adjusting case counts to account for changing testing volume over time improved correlation with other indicators. Conclusion: Outpatient sentinel surveillance of recently symptomatic individuals accurately captures trends in SARS-CoV-2 community transmission and provides early warning of increases in transmission rate. The reliability of outpatient sentinel surveillance can be limited by low testing volume, slow test turnaround time, and delays in reporting.